Chemical Composition, Functional Properties, and Effect of Inulin from Tunisian Agave americana L. Leaves on Textural Qualities of Pectin Gel - Mohamed Ali Bouaziz; Rabaa Rassaoui; Souhail Besbes (Journal of Chemistry)
In this study, the chemical composition and functional properties of Agave americana L. (AA) leaves were determined. The Agave leaves powder had a high amount of total dietary fiber (38.40%), total sugars (45.83%), and protein (35.33%), with a relatively low content in ash (5.94%) and lipid (2.03%). The Agave leaves were exhibited with potential food application. The Agave inulin showed a significant difference compared with the commercial inulin as for aw (0.275 against 0.282), pH (5.53 against 5.98), ash (2.89% against 1.19%), protein (3.46% against 1.58%), water holding capacity (2.42% against 1.59%), solubility (73 g/L against 113 g/L), and emulsion capacity (14.48% against 21.42%), respectively. The textural properties of Agave inulin-pectin mixed gels were examined using instrumental Texture Profile Analysis (TPA). Firmness of the prepared Agave inulin-pectin mixed gels was lower than the pectin gel (0.3554 N against 5.7238 N, resp.). This reduction of firmness showed a synergetic effect between pectin and inulin. These results suggested a positive interaction between Agave inulin and pectin to decrease the firmness of mixed gels and open a good alternative to obtain value added products from this resource.